Evaluation of Seed Vigour in Onion - T.N. USHA; MALAVIKA DADLANI (Seed Research, 2026)
Vigour assessment of twelve seed lots of onion was made through standard germination (first and final count), seedling dry weight, seed vigour index, accelerated ageing, controlled deterioration, dual stress, electrical conductivity, and volatile aldehyde tests. The results of these vigour tests were correlated with field emergence. The highest positive correlation with field emergence at 1% significance was recorded with standard germination final count, (r = 0.937*), followed by seed vigour index (r = 0.916), germination first count and dual stress test (r = 0.899*). To know the storage potential, seed lots were stored under ambient conditions and correlation was determined, between standard germination, accelerated ageing, dual stress test and field emergence with germination recorded at three months’ interval during storage upto 12 months. The highest correlation was recorded between initial germination per cent and germination taken after every three months of storage upto twelve months. Hence, indicating the actual germination (%), rather than the minimum prescribed standards was found to be a better indicator of onion seed field emergence and storability.